Pengaruh Model Pembelajaran Argument-Driven Inquiry (ADI) terhadap Keterampilan Argumentasi Siswa Berkemampuan Akademik Berbeda - Safira, Cherry Acerola; Hasnunidah, Neni; Sikumbang, Darlen (Department of Biology Education, Universitas Pendidikan Indonesia, 2018)
This study aimed to find out the significant effect of Argument-Driven Inquiry (ADI) learning model, student's academic ability, and the interaction between learning models and academic ability of the students’ argumentation skills. The population was all students of class VIII MTs Negeri 1 Bandar Lampung. The Samples were students of class VIII A and VIII B selected from the population by random cluster sampling technique. This study was quasi-experimental with Pretest Post-test Non Equivalent Control Group Design. The instrument used was argumentation skills test on the material motion systems in humans. The data were statistically analyzed using Ankova test and test Significant Difference (LSD) respectively at 5% significance level. The results showed that the learning ADI model, academic ability, and the interaction between the ADI model and academic abilities significantly influenced argumentation skills with significant value of each were 0,000; 0.007; and 0.038.